Cannonball jellyfish fishery in Sonora: potential for production, trade, and economic integration with Asia - Méndez Barrón, Rosana (Posgrados de la División de Ciencias Económica Administrativas, 2023)
In recent decades, Sonoran fish production has increased its presence in Asian markets. One of the fisheries that has stood out is the “cannonball” jellyfish (Stomolophus meleagris), also known as “aguamala”. In addition to its local and state economic contribution, the development of this fishery represents a strategy for strengthening trade relations within the framework of the integration process in the Asia-Pacific region. The objective is to highlight characteristics of this activity in productive terms for the state of Sonora with analysis of export and fishing figures from 2017 to 2022, highlighting its potential not only as a local productive alternative, but as another possibility to strengthen our economic integration. to the Asian continent, one of the regions with the highest economic growth and with the best prospects for future development. Research with descriptive, non-experimental and cross-sectional design in quantitative analysis. Results express strengths and collaborations in the framework of economic integration in the Asia-Pacific region as an alternative fishery to strengthen the country's collaboration in the markets with the highest global growth, the beginning of a process of reconversion and commercial diversification that is so necessary for Mexico. ; needs to reorganize not only in the economic sphere, to make it more profitable and generate value in the social sphere, as a mechanism for employment, strengthening living conditions in rural localities and developing sustainable use mechanisms that allow this type of productive experiences remain operational in the long term. Opportunity areas in abrupt descending and ascending financial behaviors and export figures refer to biological risks identified by experts, among others; in turn, an arduous path to access official public information, the need for certifications and standards that affect added value that enhances the quality of exports.